The Approximation of Sum of Independent Distributions by the Erlang Distribution Function - Karoblis, Antanas (Nonlinear Analysis: Modelling and Control, 2002)
The exponential distribution and the Erlang distribution function are been used in numerous areas of mathematics, and specifically in the queueing theory. Such and similar applications emphasize the importance of estimation of error of approximation by the Erlang distribution function. The article gives an analysis and technique of error’s estimation of an accuracy of such approximation, especially in some specific cases.
Keywords: accuracy of approximation; Erlang distribution; sum of independent distributions